P192 Evaluation of predictive factors of worse prognosis in lupus nephritis: focus on new pathogenetic pathways. (23rd March 2020) - Varriano, Valentina; Paglionico, Annamaria; Petricca, Luca; Mario, Clara Di; Gigante, Maria Rita; Tanti, Giacomo; Tolusso, Barbara; Gremese, Elisa
Abstract : Purpose: To evaluate the prognostic factors in a cohort of patients with lupus nephritis (LN) focusing on of the IL-17, 23 axis as new pathogenetic pathway. Patients and Methods: 91 LN patients were enrolled. Laboratory, immunological and disease activity data were collected at the baseline and at 6(T6), 12(T12), 24(T24) months and at the last follow-up(FU).84 renal biopsies were evaluated according to ISN/RPS classification, assessing the inflammatory interstitial infiltrate using the BANFF score. Baseline serum levels of IL-17 and IL-23 were assessed by ELISA in 37 patients. Results: Among the 84 renal biopsies evaluated 77% belonged to class III and IV; 41, 8% of patients had an interstitial infiltrate<5%, 35.2% between 5% and 25% and 15, 4% above 25%. Regarding immunological data 35, 2% of patients revealed a seropositivity for antiphospholipid antibodies (APL+). Serum level of IL-17 and IL-23 were 0.12±0.15 pg/ml and 27.7±9.12 pg/ml respectively. Through the ROC curves analysis we found a cut off value of 25.89 pg/ml of IL-23 for remission at T6. Among the 10 patients with a IL-23 level above this cut-off none achieved remission at T6 and at the univariate analysis a serum level of IL-23 above the cut-off was associated with an interstitial infiltrate>5% at renal biopsy and persistent proteinuria. Finally, we conducted an univariate and multivariate analysis for each renal outcome considered. We found that an inflammatory interstitial infiltrate>5% and APL+ were associated with worse renal outcome in terms of early and persistent remission, chronic damage, persistent proteinuria, and renal flare both in univariate and multivariate analysis. Higher serum level of IL-23 was associated with persistent proteinuria, renal flare and tended to be associated to chronic renal damage. Conclusion: Interstitial infiltrate and APL+ resulted as the strongest predictors of worse renal outcome. An higher serum level of IL-23 resulted as a negative prognostic factor highlighting its possible role as a biomarkers of more aggressive disease.